Controlled radical polymerization and in-depth mass-spectrometric characterization of poly(ionic liquid)s and their photopatterning on surfaces. Issue 2 (16th November 2015) - Steinkoenig, Jan; Bloesser, Fabian R.; Huber, Birgit; Welle, Alexander; Trouillet, Vanessa; Weidner, Steffen M.; Barner, Leonie; Roesky, Peter W.; Yuan, Jiayin; Goldmann, Anja S.; Barner-Kowollik, Christopher
Abstract : Poly(ionic liquid)s (PILs) bearing a polystyrene backbone prepared via RAFT polymerization and their photolithographic patterning on silicon wafers is reported. Abstract : The preparation and characterization of poly(ionic liquid)s (PILs) bearing a polystyrene backbone via reversible addition fragmentation chain transfer (RAFT) polymerization and their photolithographic patterning on silicon wafers is reported. The controlled radical polymerization of the styrenic ionic liquid (IL) monomers ([BVBIM]X, X = Cl − or Tf2 N − ) by RAFT polymerization is investigated in detail. We provide a general synthetic tool to access this class of PILs with controlled molecular weight and relatively narrow molecular weight distribution (2000 g mol −1 ≤ M n ≤ 10 000 g mol −1 with dispersities between 1.4 and 1.3 for p([BVBIM]Cl); 2100 g mol −1 ≤ M P ≤ 14 000 g mol −1 for p([BVBIM]Tf2 N)). More importantly, we provide an in-depth characterization of the PILs and demonstrate a detailed mass spectrometric analysis via matrix-assisted laser desorption ionization (MALDI) as well as – for the first time for PILs – electrospray ionization mass spectrometry (ESI-MS). Importantly, p([BVBIM]Cl) and p([DMVBIM]Tf2 N) were photochemically patterned on silicon wafers. Therefore, a RAFT agent carrying a photoactive group based on ortho -quinodimethane chemistry – more precisely photoenol chemistry – was photochemically linked for subsequent controlled radical polymerization of [BVBIM]Cl and [DMVBIM]Tf2 N. The successful spatially-resolved photografting is evidenced by surface-sensitive characterization methods such as X-ray photoelectron spectroscopy (XPS) and time-of-flight secondary ion mass spectrometry (ToF-SIMS). The presented method allows for the functionalization of diverse surfaces with poly(ionic liquid)s.